Trabalho docente e educação em tempo integral: um estudo sobre o programa escola integrada e o projeto educação em tempo integral - Ana Maria Clementino Jesus e Silva (2013)
With the emergence of programs and projects of full-time education in school systems in Brazil in the last decade, driven by changes in the Brazilian educational legislation and by financial and technical contributions offered by the federal government through the Programa Mais Educação (More Education Program), it was observed the insertion of new teachers with profiles, formations e tasks other than those traditionally promoted by teachers. This research aimed, from the study about the Programa Escola Integrada (PEI) of the municipal system of education of Belo Horizonte and about the Projeto Educação de Tempo Integral (PROETI) of the state of Minas Gerais education system, to know the teachers work in the experiences of full-time education. We have tried to identify the profile of the professionals involved, analyse the organization of work and understand the conditions of teachers work in the PEI and in the PROETI. We also seek to understand the conceptions of integral education of each experience and analyze the relationships of programs/projects of full-time education with the current social policies to combat poverty. To this end, we developed bibliographic and documentary searches, as well as observations at two schools in the capital of Minas Gerais, each one of an education system, and its respective program/project, and conducted semistructured interviews with the school management, coordination and teachers of the PEI and the PROETI. As a result, we found that the experiences, although based on the conception of integral education proposed by Anísio Teixeira with the purpose of complement the formation of the students, dissociate themselves from this purpose by adopting different measures about its object. While the PROETI favors activities of pedagogical accompaniment aiming at good school performance and the reduction of school retention not leaving aside the expansion of artistic opportunities, sports and leisure, the PEI highlights the personal and cultural education of the students through the expansion of educational spaces, the diversity of activities and appreciation of community knowledge, reflecting on the profile of teachers of both experiences. The first one has teachers with undergraduate degrees in pedagogy and physical education, and the second one has students with scholarships and cultural agents (workshop mediators from the community) without prior training or teaching experience requirements to conduct the activities. We verify that although the programs and projects of full-time education as the PROETI and the PEI are important tools of protection and social promotion, directed primarily to children and teenagers in greater conditions of social vulnerability, they present many problems and unsuitable working conditions for the good performance of the activities of teachers and for student reception.